How to start a home-based bakery business - Davis, Detra Denay (Guilford, Conn. : Globe Pequot Press, 2011)
Veteran cook and caterer Detra Denay Davis provides all the tools and success strategies you need to launch and grow your home-based bakery business. She shares her experiences and advice on making sense of local, state, and federal rules and regulations; structuring your business; developing a product line; packaging, labeling, and marketing products; and learning how to become and stay profitable. --Back cover.
Includes bibliographical references and index.
Keywords: Home-based businesses -- Management; Baked products -- Management; Bakeries -- Management; Baking -- Management